Postprandial Glucose Spikes, an Important Contributor to Cardiovascular Disease in Diabetes? - Hanssen, Nordin M. J.; Kraakman, Michael J.; Flynn, Michelle C.; Nagareddy, Prabhakara R.; Schalkwijk, Casper G.; Murphy, Andrew J. (Frontiers in Cardiovascular Medicine, 2020)
Clinical trials investigating whether glucose lowering treatment reduces the risk of CVD in diabetes have thus far yielded mixed results. However, this doesn't rule out the possibility of hyperglycemia playing a major causal role in promoting CVD or elevating CVD risk. In fact, lowering glucose appears to promote some beneficial long-term effects, and continuous glucose monitoring devices have revealed that postprandial spikes of hyperglycemia occur frequently, and may be an important determinant of CVD risk. It is proposed that these short, intermittent bursts of hyperglycemia may have detrimental effects on several organ systems including the vasculature and the hematopoietic system collectively contributing to the state of elevated CVD risk in diabetes. In this review, we summarize the potential mechanisms through which hyperglycemic spikes may increase atherosclerosis and how new and emerging interventions may combat this.